When fees fall: Conceptualizing "free" higher education as a public good - Ndaba, M. (South African Journal of Higher Education, 2023)
This article conceptualizes “free” higher education as a public good. It draws on a qualitative study conducted between 2018‒2019, exploring academics’ understanding of the relationship between higher education and the public good, and the conditions of possibility for higher education to be and contribute to the public good. In so doing, this article argues that funding for free education is a necessary condition for higher education to be a public good that can be accessed by students from different socioeconomic backgrounds. It argues that commodification of higher education undermines the public good character of higher education, and ultimately reproduces inequalities in society, and the injustices of the past, particularly in a country like South Africa characterised by colonial and apartheid histories. It anchors this argument on an analysis of 15 in-depth one-on-one interviews with academics from historically white and historically black universities in South Africa. From this analysis emerged three main findings on the issue of higher education funding. Firstly, the view that funding for higher education is scarce due to austerity, among other things. Secondly, the notion that if higher education is a public good and for the public good, it must be funded by the state. Lastly, the argument that adopting private funding models opens higher education to commodification, elitism, and the risk of being captured and used as an instrument of advancing private goods at the expense of the public good. The implication of these findings is the notion that when fees fall, one obstacle is removed, opening access to higher education – a public good – even for the poorest of the poor.